How Do Fair Value Measurements of Financial Instruments Affect Investments in Banks? - Ralf Bergheim; Jürgen Ernstberger; Michael W. M. Roos (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This paper experimentally investigates how fair value measurements of financial instruments affect the decision of nonprofessional investors to invest in a bank's shares. Specifically, we assess how investors respond to variations in net income resulting from fair value adjustments in trading assets and how the reliability of the fair value estimates affects their decision. We find that investment decreases as a result of transitions from the first to the third level and we even observe lower investments in case of positive changes in income. Investment decreases most if negative valuation adjustments are based on level 1 estimates suggesting that down pricing by the market is considered as a worse signal than model-based decreases in net income. For larger positive and negative adjustments the impact of valuation levels on investment turns out to be limited. Our results do not provide evidence that Fair Value Accounting per se induces pro-cyclical investment behavior. – – Die experimentelle Studie untersucht, wie die Bewertung zum Fair Value die Investitionsentscheidung nicht-professioneller Investoren beeinflusst. Dabei wird die Entscheidung, in Aktien einer Bank zu investieren, in Reaktion auf verschieden hohe Bewertungsänderungen der Aktiva Position 'Wertpapiere' der Bank untersucht. Es erfolgt des Weiteren eine differenzierte Betrachtung der Auswirkungen der Fair Value Hierarchie (Level 1-3) auf die Investitionsbereitschaft. Die Resultate zeigen, dass die Investitionsbereitschaft sowohl für negative als auch positive Bewertungsänderungen abnimmt. Die geringste Investitionsbereitschaft wird im Fall von negativen Bewertungsänderungen auf Grundlage beobachtbarer Marktpreise beobachtet (Level 1).
Keywords: C91; G11; M41; 330; banks; fair value accounting; nonprofessional investors; investment decision; experiment